Information Disruption in Online Journalism in The Era Of Industrial Revolution 5.0: A Critical Review in The Indonesian Context: Information Disruption in Online Journalism in The Era Of Industrial Revolution 5.0: A Critical Review in The Indonesian Context - Fyan Andinasari Kuen; Mitha Mayestika Kuen (Public Resource Innovation Management and Excellence, 2025)
The advent of the Industrial Revolution 5.0 and the vision of Society 5.0 have precipitated transformative shifts not only within industrial sectors but also across the landscape of online journalism, particularly in Indonesia. This article critically examines the manifestations of information disruption in this context. Through an in-depth analysis of recent scholarly publications from reputable journals, national policy documents, and international reports, this study identifies five interrelated themes: (1) the pervasive influence of technologies such as artificial intelligence and automation, (2) the growing digital divide, (3) the impact of platform power and the attention economy, (4) the transformation of professional norms and journalist identities, and (5) emerging ethical dilemmas associated with technological adoption. Findings reveal that the ongoing disruption is multifaceted. While technology enables unprecedented efficiency and innovation, Indonesia's unique challenges—including infrastructural inequalities, concentrated media ownership, and uneven digital literacy—exacerbate fragmentation within the information ecosystem. Consequently, the realization of a human-centered Society 5.0 in journalism faces significant obstacles. The article concludes by proposing policy recommendations focused on infrastructure development, AI governance, and capacity building, alongside suggesting avenues for future research.